The Effect of ESG, Sustainable Financial Performance, and Ownership Structure on Tax Avoidance in Banking Companies Listed on the IDX in 2022–2024 - Nursalim, Nursalim; Risanda Alirastra Budiantoro (International Journal of Economics, Commerce, and Management, 2025)
This study aims to examine the influence of profitability, Sustainable Financial Performance, and firm size on tax avoidance in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research uses a quantitative approach, relying on secondary data obtained from the annual financial reports of banking companies. The analysis method applied is multiple linear regression to assess the effect of the independent variables profitability, Sustainable Financial Performance, and firm size on the dependent variable, tax avoidance. The findings reveal that profitability, Sustainable Financial Performance, and firm size have a simultaneous and significant impact on tax avoidance. Partially, each variable also exerts a significant influence, suggesting that financial performance, capital structure, and company scale play key roles in determining tax avoidance behavior. The results are expected to enrich tax accounting literature and serve as practical input for banking management in formulating legal and efficient tax strategies.